Exploring the composition and formation of lesbian social ties - Logan, Laura S. (Kansas State University, 2008)
The literature on friendship and social networks finds that individuals form social ties with people who are like them; this is termed "homophily." Several researchers demonstrate that social networks and social ties are homophilous with regard to race and class, for example. However, few studies have explored the relationship of homophily to the social ties of lesbians, and fewer still have explicitly examined sexual orientation as a point of homophily. This study intends to help fill that gap by looking at homophily among lesbian social ties, as well as how urban and non-urban residency might shape homophily and lesbian social ties. I gathered data that would answer the following central research questions: Are lesbian social ties homophilous and if so around what common characteristics? What are lesbians' experiences with community resources and how does this influence their social ties? How does population influence lesbian social ties? Data for this research come from 544 responses to an internet survey that asked lesbians about their social ties, their interests and activities and those of their friends, and the cities or towns in which they resided. Using the concepts of status and value homophily, I attempt to make visible some of the factors and forces that shape social ties for lesbians.
Keywords: Social Networks; Sexualities; Homophily; Sociology, General (0626)